2018
DOI: 10.1177/0269216318755624
|View full text |Cite
|
Sign up to set email alerts
|

“People don’t understand what goes on in here”: A consensual qualitative research analysis of inmate-caregiver perspectives on prison-based end-of-life care

Abstract: Findings suggest that inmate-caregivers believe they provide a unique and necessary adaptation to prison-based end-of-life care resulting in multilevel benefits. These additional perceived benefits go beyond a marginalized group gaining access to patient-centered end-of-life care and include potential inmate-caregiver rehabilitation, correctional medical staff feeling supported, and correctional facilities meeting end-of-life care mandates. Additional research is imperative to work toward greater standardizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(46 citation statements)
references
References 45 publications
0
46
0
Order By: Relevance
“…The review identified 23 articles, 16 reporting qualitative methods2 3 29–42(table 3), six reporting quantitative methods8 9 43–46(table 4) and one reporting mixed methods4(table 3). Methodological diversity was high across all groups.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The review identified 23 articles, 16 reporting qualitative methods2 3 29–42(table 3), six reporting quantitative methods8 9 43–46(table 4) and one reporting mixed methods4(table 3). Methodological diversity was high across all groups.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen articles reported findings from six studies based in the USA,8 9 29–33 36 39–43 four articles reported findings from three studies based in the UK,4 35 38 45 three articles reported findings from two studies based in Switzerland,3 34 37 two articles reported findings from one study in France2 46 and one article reported findings from a study in India 44. The articles reported on a broad range of areas, including prison healthcare facilities,43 45 the health of dying prisoners and causes of death,8 9 44 46 elderly and dying prisoners views on issues related to palliative and end of life care in prisons3 4 34 36 40 and inmate volunteer caregivers 30–33 42. Of the 19 studies which sampled prisoners (or their case records),2–4 8 9 29–34 36–38 40–42 44 46 12 dealt exclusively with male prisoners,4 8 29 30 32 33 36–38 40–42 and seven with male and female prisoners 2 3 9 31 34 44 46…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations